PENINGKATAN KUALITAS LIST PROFILE DENGAN PERLAKUAN KOMPOSISI BAHAN PEREKAT - Sushardi; Yuniarto (Jurnal Wana Tropika, 2011)
List profile is a mineral board product that more and more interested people use it. One of its advantage is the cheap cost, quick availability and more resistant against damaging organism attacks. From economyâ€™s point list profile with adhesive plaster and filler rofing more expensive, so it required another type of adhesive which is stronger but cheaper cost. This research has the objection to find out the filler type and content of gips with low cost. The design of this research is complete random design continued by Tukey test. The factors were the filler type using â€œmendongâ€ and rofing, and adhesive contents of 720 grams, 780 grams, and 840 grams to observed the water content, density, modulus of elasticity, modulus of rapture and its adhesive strength. The result indicated an interaction between the filler type and its content both influenced the water content and density. The average of water content, density, modulus of elasticity, modulus of rapture and adhesive strength were 17,6787-20,0729 %, 0,9575 â€“ 1,1489 g/cm3 , 3172,7619 â€“ 4831,6183 kg/cm2 , 25,8452 â€“ 30,8413 kg/cm2 , and 1,9006 â€“ 3,4287 kg/cm2 respectively. Keywords: List profile, mendong, rofing, gips